Dynamic Boronate Ester Based Hydrogel with Enhanced Mechanical Properties and Multi-Stimuli-Triggered Release for Tissue Repair and Antioxidant Therapy - Fangyi Liu; Gaoyang Li; Zhenhui An; Sijia Wang; Shouhong Xu; Honglai Liu (Gels)
Oxidative stress and chronic inflammation play pivotal roles in causing impaired tissue regeneration and delaying wound healing processes. Epigallocatechin gallate (EGCG) demonstrates robust anti-inflammatory and antioxidant characteristics, thereby emerging as a highly promising therapeutic substance for tissue repair applications. In order to counteract the pathological characteristics of the wound microenvironment, including increased levels of reactive oxygen species (ROS), low pH (weak acidic conditions), and elevated glucose concentrations, a hydrogel with pH/ROS/glucose-responsive properties was fabricated. This hydrogel was modified with phenylboronic acid (PBA) groups, which not only enhance its mechanical strength but also endow it with multi-stimuli responsiveness via dynamic boronate ester bonds. The impacts of grafting of PBA and loading of EGCG on the rheological and mechanical properties, as well as the network structure of the hydrogels, were systematically investigated. Moreover, in vitro experiments showed that the hydrogel could achieve excellent sustained and controlled release of both small-molecule and macromolecular drugs. Additionally, cell viability tests verified the hydrogel’s outstanding biocompatibility, and antioxidant experiments demonstrated its efficient ability to scavenge intracellular ROS. In conclusion, this injectable and biodegradable hydrogel possesses multi-stimuli responsiveness, controllable drug release behavior, and antioxidant capacity, presenting a promising approach to alleviate oxidative damage and promote tissue repair. This study offers valuable perspectives for the design of advanced hydrogel materials aimed at treating wound healing.